Student’s Cognitive Conflict in Geometry Learning - Pipit Firmanti (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to describe the cognitive conflicts of students in solving the equation of a circle. The research method used is descriptive qualitative. This study involved students who experienced cognitive conflict as a sample. The instruments used are tests and interviews. The results showed that there were eight forms of cognitive conflict that emerged when students completed the given questions. There is a tendency where students can determine the center and radius of a circle correctly but have difficulty drawing a circle from the given equation.